Divalent cations (Mg2+, Ca2+) protect bacterial outer membrane damage by polymyxin B - Ahmad Zorin Sahalan,; Abdul Hamid Abd. Aziz,; Hing, Hiang Lian; Mohd Kamel Abd. Ghani, (Universiti Kebangsaan Malaysia, 2013)
Polymyxin B interacts with divalent cations by displacing cations from their binding sites in the lipopolysaccharide (LPS) molecules. It leads to the disorganization of the outer membrane component of the Gram negative bacteria, which releases LPS component from bacterial surface causing severe membrane leakage and finally cell death. In this paper, the reversible activity of PMB was investigated in the presence of access divalent cations such as Mg2+ or Ca2+. Membrane damage and cell disruption were monitored by detecting leakage of the outer membrane and cytoplasmic enzyme marker (β-lactamase and β-galactosidase), release of LPS component (KDO) from bacterial cells and bacterial survival. With the presence of divalent cations, leakage of enzyme markers and LPS released was significantly reduced when bacteria were exposed to PMB. The survival curve also significantly increased. The inhibitory of damage caused by PMB also depended on the type of divalent cation present. Ca2+ has been shown to be more effective in protecting the bacteria cells than Mg2+. This is because Ca2+ appears more frequently as a constituent of the structural components of the bacteria. In conclusion, the presence of higher concentration of divalent cation particularly with Ca2+ inhibits PMB activity and maintained bacterial survival.